A COMBINATION TECHNIQUE OF AUTOLOGOUS AUGMENTATION AND BREAST LIFTING IN HYPOPLASTIC-THIRD GRADE PTOTIC BREAST: A CASE REPORT - Beta Subakti Nataatmadja; Amatullah, Nida' Fahima; Lumintang, Loelita Marcelia (Universitas Airlangga, 2024)
Highlights: This case shows autoaugmented mastopexy as a natural alternative to silicone implants for patients seeking breast enhancement. The combination of breast lift and autoaugmentation using the patient’s own tissue is presented as an effective method for achieving a firmer breast appearance while maintaining a natural look. The use of tailored preoperative design, including breast ultrasound, enhances surgical safety and outcomes. Abstract: Introduction: Breast ptosis is a common concern among women due to factors such as aging, pregnancy, breastfeeding, and weight loss. To achieve a beautiful breast shape, mastopexy (breast lift) with augmentation is often required. This case report highlights the relevance of the chosen augmentation method in addressing ptosis. Case Illustration: A 30-year-old woman had breast ptosis after her 2nd child and wanted a breast lift to have lifted and firmer breasts. Due to limited fat tissue available for transfer and her refusal to use silicone implants, the patient chose autoaugmented mastopexy. Before surgery in August 2022, breast ultrasound showed abnormalities. Preoperative design was made to determine skin and pedicle positions, using a wise pattern with a superior pedicle to lift the nipple-areola complex (NAC) and an inferior pedicle for autoaugmentation. Surgery was done carefully to achieve symmetry and desired result. Discussion: Breast tissue changes a lot during and after pregnancy and hormonal factors increases the risk of ptosis. According to Regnault classification, the patient was classified as 3rd degree ptosis. While prosthetic implants are common in breast surgery, the patient declined that option. Autoaugmented mastopexy offers a more natural result without the risks of implants. Conclusion: Breast lift with autoaugmentation is suitable for patients with breast ptosis seeking a firmer appearance without added volume. This technique utilizes the patient's own tissue to achieve satisfactory results, although outcomes may vary depending on individual factors.